Insulin-independent stimulation of skeletal muscle glucose uptake by low-dose abscisic acid via AMPK activation - Magnone, Mirko (Sci Rep, 2020)
Abscisic acid (ABA) is a plant hormone active also in mammals where it regulates, at nanomolar concentrations, blood glucose homeostasis. Here we investigated the mechanism through which low-dose ABA controls glycemia and glucose fate. ABA stimulated uptake of the fluorescent glucose analog 2-NBDG by L6, and of [(18)F]-deoxy-glucose (FDG) by mouse skeletal muscle, in the absence of insulin, and both effects were abrogated by the specific AMPK inhibitor dorsomorphin. In L6, incubation with ABA increased phosphorylation of AMPK and upregulated PGC-1α expression. LANCL2 silencing reduced all these ABA-induced effects. In vivo, low-dose oral ABA stimulated glucose uptake and storage in the skeletal muscle of rats undergoing an oral glucose load, as detected by micro-PET. Chronic treatment with ABA significantly improved the AUC of glycemia and muscle glycogen content in CD1 mice exposed to a high-glucose diet. Finally, both acute and chronic ABA treatment of hypoinsulinemic TRPM2(-/-) mice ameliorated the glycemia profile and increased muscle glycogen storage. Altogether, these results suggest that low-dose oral ABA might be beneficial for pre-diabetic and diabetic subjects by increasing insulin-independent skeletal muscle glucose disposal through an AMPK-mediated mechanism.